2008
DOI: 10.1111/j.1399-6576.2008.01641.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of post‐operative pain after a laparoscopic tubal ligation procedure

Abstract: The study indicates that pre-surgical pain and heat pain sensitivity are important pre-operative indicators of post-operative pain intensity, while psychological factors like vulnerability and anxiety seem to contribute to a lesser degree after laparoscopic tubal ligation. The prediction model accounted for 29-43% of the total variance in post-operative movement-related pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 16 publications
7
72
1
4
Order By: Relevance
“…While studies have found preoperative HPT and cold pressor pain to predict acute resting pain after cesarean section [48,64], laparoscopic tubal ligation [59], and laparoscopic cholecystectomy [5], other studies have demonstrated a direct relationship between pain sensitivity and movement pain but not resting pain [15,18,40,72]. A reduction in pricking pain thresholds corresponded to lower movement pain but not resting pain in patients after renal surgery [72], and a reduction in von frey pain thresholds correlated with movement pain but not resting pain after major gynecologic surgery [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies have found preoperative HPT and cold pressor pain to predict acute resting pain after cesarean section [48,64], laparoscopic tubal ligation [59], and laparoscopic cholecystectomy [5], other studies have demonstrated a direct relationship between pain sensitivity and movement pain but not resting pain [15,18,40,72]. A reduction in pricking pain thresholds corresponded to lower movement pain but not resting pain in patients after renal surgery [72], and a reduction in von frey pain thresholds correlated with movement pain but not resting pain after major gynecologic surgery [40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have included pain sensitivity measures as possible predictors of pain following obstetrics and gynecology surgery consistently identify higher thermal pain sensitivity to be predictive of postoperative pain [5,48,59,64]. A systematic review of 43 studies with 23,057 patients undergoing a variety of surgical procedures found that higher preoperative pain and anxiety, younger age, and abdominal, orthopedic, and thoracic surgery consistently predicted higher postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…17 Pos to pe ra tif ağ rı ki şi nin fi zik sel ve psi ko lo jik özel-lik le rin den et ki len mek te ve ki şi ye gö re fark lı lık gös ter mek te dir. [2][3][4][5]16,18 Cin si ye tin ba sınç ağ rı eşi ği ni ve ank si ye te dü-ze yi ni et ki le di ği, ka dın cin si ye tin ba sınç ağ rı eşi ği -nin da ha dü şük ol du ğu, 19,20 an cak ank si ye te dü ze yi nin da ha yük sek 11,[21][22][23][24] ol du ğu be lir til miş tir.…”
Section: Tar Tiş Maunclassified
“…Ağ rı eşi ği sı cak, so ğuk, kuta nöz ve ba sınç ağ rı eşi ği ola rak çe şit li şekil ler de öl çül müş tür. [2][3][4][5][6][7] Ank si ye te nin ağ rı eşi ği nin düş mesi ne ne den olan bir fak tör ol du ğu be lir til miş tir. 8 Ay rı ca cer ra hi iş lem stre si ce va bı be lir le yen bir seri hor mo nal ve me ta bo lik de ği şik lik le ri sti mü le eder.…”
unclassified
“…15 Average operative times for each procedure were estimated using data from our institution, and we supplemented procedure data not currently performed at our institution with average procedure times from published series. [16][17][18][19][20][21] The number of cylinders and CO 2 emissions were calculated from these data.…”
Section: Methodsmentioning
confidence: 99%